Effectiveness of the Geoeducational Assessment Method (GEOAM) in Unveiling Geoeducational Potential: A Case Study of Samos - Zafeiropoulos, George; Hara Drinia (Geosciences, 2023)
This paper explores the efficacy of the geoeducational assessment method (GEOAM) in evaluating the geoeducational potential of geosites. Leveraging a case study involving four geotopes on the island of Samos, Aegean Sea, Greece, this study examines the strengths and limitations of the GEOAM approach, aiming to comprehensively elucidate its efficacy. The assessment outcomes illuminate the vital role of targeted strategies in enhancing the educational and sustainable impact of geosites, thereby fostering geological understanding and responsible environmental engagement. A prominent finding is the urgency to address the gap in foundational geological knowledge, underscored by the need for robust geoeducation programs at schools and the augmented presence of geologists. While acknowledging potential limitations, including subjectivity in scoring and data availability constraints, this study underscores the method’s broader contribution to societal goals. By integrating geoethic principles, GEOAM offers a comprehensive framework aligning with the objectives of geological comprehension and environmentally conscious practices.